Hubungan Antara Dukungan Sesama Mahasiswa dan Ketangguhan Akademik di Kalangan Mahasiswa Tingkat Akhir Selama Penulisan Skripsi - Hernia Herdin; Suryani Hi Umar (STAI AL-AMIN, 2026)
This Study was motivated by the phenomenon of senior students who often face various obtacles and challenge during the thesis writing the proces. Which requires academic resilience that is, the ability to persevere and bounce back from difficults circumstances. Peer suppoert has been identified as one of the external factors that plays a significant role in strengthening this academic resilience. This study aims to describe the levels of peer suppoert and academic resilience among senior undegraduate students during the thesis writing period, as well as to analyze the relationship between peer support and academic resilience among senior undergraduate students during the thesis writing period at the Faculty of Tarbiyah and Teacher Education IAIN Ternate. This study employs a quantitative approch with a correlational design. The student population consisted of 285 individuals, with a sample of 75selected using a probability sampling technique of the random sampling type. The data collection instruments connsisted of peer support scale and academic resilience scale using a likert scale (1-4) packged in the form of questionnaire, while data analysis conducted using pearson’s product moments correlation test. The results of the study indicate that the level of peer support was 68,0% and the moderate category, in the level of academic resilience among student was 78;7% in the moderate category, furthemore, there was a positive and significant relationship beetwen peer support and academic resilience, with a correlation coeficient of r = 0,759 and a significant level of 0,000 (p = 0,05). Based on these result, it can be concluded that the higher the level of peer support, the higher the academic resilience among final year students during the thesiswriting period at the Faculty of Tarbiyah and Teacher Education IAIN Ternate.